Kinetics and Mechanism of Os(VIII)-Catalyzed Oxidation of 2-Methyl propanol-1 by N-Chlorosuccinimide in Aqueous Alkaline Medium - Kumar, Ashutosh; Singh, Abhishek (Asian Journal of Chemistry, 2010)
Kinetics of Os(VIII) catalyzed oxidation of 2-methyl propanol-1 by N-chlorosuccinimide in aqueous alkaline medium have been investigated in the temperature range 30, 35, 40 and 45 ºC. The reaction exhibited first-order in [N-chlorosuccinimide](NCS), [Os(VIII)] and [OH] and zero order in [2-methyl propanol-1]. Negligible effects of added product, succinimide and mercuric acetate on the reaction rate were observed. The variation of ionic strength of the medium showed zero effect on the reaction rate. The mechanism involving the [OsO4(OH)2]2- ion as the reactive species of the catalyst and N-chlorosuccinimide, the oxidant in the slow and rate determining step has been suggested.